Zeitschrift für das gesamte Genossenschaftswesen (De Gruyter Oldenbourg, 1950)
The Journal is the only internationally distributed German-language periodical to deal with the study of co-operatives; an academic discussion forum for the legal, sociological and economical aspects of co-operatives. It was first published in 1950 by members of the Institute for Research into Co-operatives at the University of Erlangen. As the publiation is published on behalf of the Working Group of Institutes for Co-operative Studies (AGI).